TINGKAT PENGETAHUAN IBU PRIMIGRAVIDA TENTANG TANDA BAHAYA KEHAMILAN SEBELUM DAN SESUDAH PENYULUHAN DI WILAYAH KERJA PUSKESMAS REJOSARI - Fadilayana Damanik; Tuti Restuastuti; Noviardi " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTComplication of pregnancy is caused of the high maternal mortality. Oneof effort to decrease the maternal mortality is to know about thr danger signs ofpregnancy. First time of pregnancy is a new experience for primigravidae, sothat, primigravidae had not yet knowledge about the pregnancy include thedanger signs of pregnancy. This study purpose to assess the evectivity ofcounseling toward the increaseof primigravidae knowledge about danger signs ofpregnancy in Puskesmas Rejosari Pekanbaru. Methods in this study using preexperimentaltechnique with pre-post test one group study. This study have sample50 people with the technique total sampling. The variables of this study wereanalyzed with Mc.Nemar test with α=0,05. The results show that respondentshave good knowledge consist of 5 respondents (10%) before counseling and aftercounseling there is an increasing number of respondents good knowledge consistof 8 respondents (16%). Anilysis test shows there is no effectiveness of counselingto improving the knowledge (p=0,532) >α=0,05 about the danger signs ofpregnancy for primigravidae. The conclusion of this study counseling is noteffective in increasing knowledge primigravidae statistically.Keywords : Knowledge, before and after counseling, pregnancy danger signs